Path Analysis on the Effect of Breastfeeding Complementary Food Pattern, Maternal Schooling, Family Income, and Birthweight, on Nutritional Status in Children Underfive - Nurjanah, Ahmitta Laila; Tamtomo, Didik; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2016)
Background: Indonesia is one among the 17 countries with the highest prevalence of stunting, wasting, and overweight in children under five. In 2013, the prevalence of moderate undernutrition and severe undernutrition was 13.9% and 5.7%, respectively, in children under five. The prevalence of stunting was 19.2%. The period from birth to 2 years is so called as a sensitive period when the deleterious exposure and inadequate food intake can result in negative impact on the quality of the future generation. This study aimed to analyze the effect of breastfeeding complementary food pattern, maternal schooling, family income, and birthweight, on nutritional status in children underfive.Subjects and Method: This was an analytic observational with cross sectional design. This study was carried out in Klaten, Central Java from December 2016 to January 2017. A total sample of 120 out of 1236 mothers who had children aged 6-24 months were selected for this study by multi-stage sampling. The dependent variable was nutritional status measured in weight for age. The independent variables were breastfeeding complementary food pattern, maternal schooling, family income, and birthweight. ÃÂ The data were collected by a set of questionnaire and analyzed with path analysis model on IBM SPSS AMOS 22.Results: The path model showed goodness of fit with CMIN= 1.18; p=0.002; GFI=0.99; NFI=0.98; CFI=1.00; RMSEA=<0.01. Breastfeeding complementary food pattern (b=0.27; p=0.002) and birthweight (b=0.25; p=0.004) showed direct positive and statistically significant effect on weight fo age score. Family income < Rp 1.400.000 (b=0.06; p=0.481) showed direct positive but statistically non significant effect on weight for age score. Maternal education showed positive and statistically significant effect on family income (b=0.28; p=0.001).Conclusion: Breastfeeding complementary food pattern and birthweight are important determinant of nutritional status as measured in weight for age in children under five. Maternal education has a positive effect on family income. Family income does not show its effect on nutritional status in this study.Keywords: breastfeeding complementary food pattern, nutritional status, children under fiveCorrespondence:ÃÂ Ahmitta Laila Nurjanah. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: lailaarmella@gmail.com.Journal of Maternal and Child Health (2016), 1(3): 170-178https://doi.org/10.26911/thejmch.2016.01.03.04